AMINO ACID PROFILE ANALYSIS OF RED AND GREEN MELINJO PEELS TEA - Saragih, Raskita; Tamizi, Ermiziar; Leonita, Shinta (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2021)
The study aims to analyze the profile of non-essential and essential amino acids in the peels and herbal tea products made from red and green melinjo peels. The processing of melinjo seeds into chips in Pandeglang Regency in Banten Provence, produces large amounts of melinjo peels waste. The processed tea from red and green melinjo peels contains polyphenol compounds, antioxidants, protein and amino acids that are good for health. The processing stages of the melinjo peel tea by sorting the peels for red and green melinjo peels, then washed, made them into thin slices, and dried using an oven blower at 65oC of temperature for 4 hours. Both green and red melinjo peels tea were analyzed for the amino acid profile using the UPLC method. Based on the results of the analysis, it was found that the amino acid content of melinjo peels and melinjo peels tea, both green and red, consisted of 7 non-essential amino acids and 8 essential amino acids. L-glutamic acid and L-aspartic acid are the highest amino acid components which can give melinjo peels tea a characteristic aroma and taste.